(untitled) (Dhaka University Journal of Business Studies, 2021)
Environmental issues and sustainable development gathers great drive in the recent era both for developed and developing countries. The objective of this study is to explore and accumulate all the relevant concepts of environmental accounting as well as identify the scenario, significance, and challenges of its proper practices in the listed companies in manufacturing sector of Dhaka Stock exchange with accelerating the goal of sustainable development. To fulfill the objectives, the study did qualitative research using content analysis in the year 2019 and has collected data on 99 listed “A category” companies from 8 different manufacturing sectors, to reveal the specific environment, sustainability, and corporate social responsibility related disclosure, and to uncover the actual scenario of environmental reporting. The research concludes that in the manufacturing sector financially secured companies also have very pitiable voluntary disclosure (mostly qualitative) under different framework patterns. Thus the study observed the lack of a standard framework for reporting environmental disclosure and suggests an obligatory standard framework should be developed for all the companies. The research also recommends improving ethical practices, imposing environmental taxes and subsidies, and developing a proper management accounting system to assess the appropriate costs of different environmental degradation, so that the goal of sustainable development can be achieved in Bangladesh. Journal of Business Studies, Vol. XLII, No. 1, April 2021 Page 17-40